2022
DOI: 10.31004/abdira.v2i2.122
|View full text |Cite
|
Sign up to set email alerts
|

PKH Shop sebagai Pemberdayaan Masyarakat untuk Meningkatkan Perekonomian Keluarga Prasejahtera Penerima Bantuan Sosial PKH Melalui Team Based Project Pejuang Muda Kementerian Sosial di Kecamatan Banjarsari Kabupaten Ciamis

Abstract: The community empowerment program through the team-based project PKH Shop Pejuang Muda, Ciamis Regency, Ministry of Social Affairs of the Republic of Indonesia is an effort to provide skills and creativity to underprivileged communities in the hope of improving the standard of living or financial aspects of the community. Purpose This community service aims to empower underprivileged communities through the Ministry of Social's youth warrior program. Through the PKH Shop team-based project program, underprivil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…In addition, it is also able to increase the productivity of KPM, according to the definition of the concept of productivity, namely the comparison between the results achieved with the resources as a whole, while labor productivity is the comparison between the results achieved with the labor market per unit time and as a benchmark if the expansion and activity attitudes resources used. The existence of this program is expected to reduce the expenditure burden on Beneficiary Families (KPM) through fulfilling needs as food needs, providing more balanced nutrition, increasing targets and receiving time, while the mechanism for using online data systems can produce one type of card that is connected to banks and can improve the level of effectiveness of social assistance in addition to BPNT, assistance PKH (Azhari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is also able to increase the productivity of KPM, according to the definition of the concept of productivity, namely the comparison between the results achieved with the resources as a whole, while labor productivity is the comparison between the results achieved with the labor market per unit time and as a benchmark if the expansion and activity attitudes resources used. The existence of this program is expected to reduce the expenditure burden on Beneficiary Families (KPM) through fulfilling needs as food needs, providing more balanced nutrition, increasing targets and receiving time, while the mechanism for using online data systems can produce one type of card that is connected to banks and can improve the level of effectiveness of social assistance in addition to BPNT, assistance PKH (Azhari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…600,000 for each Family Card (KK), while the Rice Social Assistance (BSB) is planned to be issued to 42,192 Bekasi City Beneficiary Groups (KPM) with a total of 15 Kg/month, while this assistance is issued as many as 150 thousand for the needs of Bekasi city social assistance recipients, the Office Social through the related villages refers to a name-per-address (BNBA) basis, on the SIKS NG online. (Azhari et al, 2022) system by the operator for right quantity indicated by the amount of money received by the KPM could be seen on ATMs or printed savings books. (Nurofik et al, 2022) with the timeliness and effectiveness of the distribution of social assistance, it is prioritized, although there are still problems in the field, several matters need to be investigated, researched and evaluated so that problems are minimized, some problems that occur are KPM compliance following the Family Capability socialization (P2K2) every week, ATM complaints missing, up to date can be resolved properly, so that the impact of BPNT and PKH social assistance in encouraging community productivity can run effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ini dilandaskan pada asumsi bahwa salah satu penyebab ketidaksejahteraan ekonomi adalah adanya ketimpangan dalam kepemilikan sumber daya. (Azhari & Rosali, 2022). Maka, diperlukan adanya peningkatan kualitas dengan memotivasi masyarakat agar memiliki semangat untuk maju dan kreatif dalam mengembangkan potensi yang ada dan memanfaatkan waktu dengan lebih efektif melalui kegiatan atau pekerjaan yang berdampak positif pada kesejahteraan ekonomi rumah tangga.…”
unclassified